The Beneficial Outcome of Subsequent Treatment with Anakinra during the Chronic Phase of Febrile Infection-Related Epilepsy Syndrome (FIRES): A Case Report - Tina Luize Cupane; Jurgis Strautmanis; Signe Setlere; Mikus Diriks; Madara Auzenbaha (MDPI AG, 2023)
This case report presents the clinical course of an eight-year-old boy diagnosed with febrile infection-related epilepsy syndrome (FIRES) at the age of four. Following a febrile infection, the patient experienced his initial episode of serial generalized clonic seizures. The severity of his condition led to 11 hospital admissions, totaling 157 days of hospitalization. Anakinra was initially administered during the acute phase in 2019 but was discontinued after 29 days. In 2022, the patient experienced a chronic-phase exacerbation and underwent a second course of anakinra treatment, which demonstrated a positive effect on seizure activity. With a year of anakinra therapy, the patient exhibited significant improvement in both seizure frequency and severity. This report adds to the existing evidence supporting the potential use of anakinra in the treatment of FIRES, highlighting its effectiveness during the chronic phase and suggesting the potential benefits of subsequent administration.